Neo-Sufisme: Corak dan Model Spiritualitas Masyarakat Modern - Harisman Harisman; M Iqbal Irham (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
This article wants to find several styles and models of spirituality in modern society that arise due to inner uncertainty in interpreting life in the modernization era. Modernity has indulged in ease and promised luxury in life as well as worship of science and technology and abandoned religious teachings. This research is of a normative type with a sufistic approach and is descriptive in nature which produces five features and two models namely: 1) heteronomy spirituality, 2) autonomous spirituality, 3) interactive spirituality, 4) extactic spirituality, and 5) constructive spirituality and 1) post-spirituality, and 2) urban sufism.Artikel ini ingin menemukan beberapa corak dan model spiritualitas masyarakat modern yang muncul akibat ketidakpastian batin dalam memaknai kehidupan di era modernisasi. Kemodrenan telah mengumbar kemudahan dan menjanjikan kemewahan dalam kehidupan sekaligus pemujaan terhadap ilmu pengetahuan dan teknologi serta meninggalkan ajaran agama. Penelitian ini berjeniskan normatif dengan pendekatan sufistis serta bersifat deskriftif yang menghasilkan lima corak dan dua model yakni: 1) spiritualitas heteronomy, 2) spiritualitas otonom, 3) spiritualitas interaktif, 4) spiritualitas ekstaktik, dan 5) spiritualitas konstraktif serta 1) post-spiritualitas, dan 2) urban sufism.